A pilot study of the Carpathian ichneumonine parasitoids (Hymenopera, Ichneumonidae: Ichneumoninae) reveals eighty-eight new records for Ukraine - Varga, Oleksandr; Riedel, Matthias; Diller, Erich (Zootaxa, 2020)
Data on the subfamily Ichneumoninae Latreille, 1802 (Hymenopera: Ichneumonidae) from the Ukrainian Carpathians is summarized, with 196 species from eight tribes, of which 88 species are recorded from Ukraine for the first time. The new Ukrainian records belong to four tribes, Heresiarchini Ashmead, 1900, Ichneumonini Latreille, 1802, Phaeogenini Förster, 1869, and Platylabini Berthoumieu, 1904. Phaeogenini is the most poorly studied with 75% of species recorded for the country for the first time. High-altitude zone distribution is discussed: oak forest zone is the most species-rich (125 species), while the subalpine zone is the most poorly studied (57% of species found only in this zone are new records for Ukraine). The flying adults of Ichneumoninae were found from April until October, with a maximum number of species and genera collected in July, and with most specimens collected in May. Stenobarichneumon ridibitor Aubert, 1994 is transferred to the genus Baranisobas Heinrich, 1972 (comb. nov.)